2017
DOI: 10.1159/000447169
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Neck Contracture Following Radical Retropubic versus Robotic-Assisted Laparoscopic Prostatectomy

Abstract: Introduction: Radical retropubic prostatectomy (RRP) and robotic-assisted laparoscopic prostatectomy (RALP) are co-standard surgical therapies for localized prostatic adenocarcinoma. These surgical modalities offer similar outcomes; however, lower rate of bladder neck contracture (BNC) is amongst the touted benefits of RALP. The differences between approaches are largely elucidated through multiple-surgeon comparisons, which can be biased by differential experience and practice patterns. We aimed to eliminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…In a study analyzing the experience of a single surgeon in two techniques, no difference was found in terms of anastomosis leakage, 12-month continence rate, and bladder neck contracture. 25 In our study, although the rate of urine leakage and continence rate was in favor of RARP, the rate of contracture was similar in the two groups. The previous study reflected the experience of a single surgeon over four years, and therefore, including cases that exceeded the learning curve may have resulted in similar results in both groups.…”
Section: Discussioncontrasting
confidence: 39%
“…In a study analyzing the experience of a single surgeon in two techniques, no difference was found in terms of anastomosis leakage, 12-month continence rate, and bladder neck contracture. 25 In our study, although the rate of urine leakage and continence rate was in favor of RARP, the rate of contracture was similar in the two groups. The previous study reflected the experience of a single surgeon over four years, and therefore, including cases that exceeded the learning curve may have resulted in similar results in both groups.…”
Section: Discussioncontrasting
confidence: 39%
“…Another problem affecting hospitalization stay are postoperative complications, one of which is urinary leakage. Spector et al [18] have reported postoperative urinary leakage at a rate of 4.7% in their robotic radical prostatectomy series. In our study, the urinary leakage rate in the r-PRP group was lower (2.5%) than the rates stated in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…1 In a recent prospective study comparing 2764 RARP and 942 RRP cases, the incidence of VUAS was lower in RARP than in RRP (1.9% vs 3.6%). 2 Even though the incidence of VUAS has been reduced by RARP, VUAS still develops in a certain percentage of cases. Generally, treatment options can be divided into endoscopic therapy, open reconstruction or urinary diversion; however, VUAS should commence with endoscopic therapy.…”
Section: Editorial Comment Editorial Comment From Dr Kadono To Deep Lateral Transurethral Incision For Vesicourethral Anastomotic Stenosimentioning
confidence: 99%
“…1 The incidence of VUAS was reported to be 0.5-33% when open surgery (RRP) was the standard treatment, but has decreased significantly with the advent of robotic surgery, which allows a better field of vision and delicate, reliable suturing. 2 Despite its recently decreased incidence, VUAS remains problematic for both patients and urologists. Several risk factors for VUAS, including older age, cigarette smoking history, comorbidities (e.g.…”
Section: Introductionmentioning
confidence: 99%